The Gestational Surrogate’s Autonomy - Sakellaraki, Kalomoira (Epistēmēs Metron Logos, 2023)
The necessary consent of the surrogate mother is a safeguard of both her autonomy and her self-disposition and guarantees not only the protection of human value (article 2, paragraph 1 of the Greek Constitution) but also the protection of her personality (article 5 paragraph 1 of the Greek Constitution and article 57 the Greek Civil Code). It is worth noting, after all, that sometimes it is necessary to restrict the freedom of some people, in order to ensure the freedom of others. The gestational surrogate expectant is not forced for her act. Autonomy presupposes the possibility of formulating and implementing a decision, as a form of personal freedom, having as a result that pressure opposes the obstruction of the surrogate mother and the future parents to do what they want and therefore feel free and not be oppressed indirectly. On the other hand, Ronald Dworkin reports on the importance of autonomy in reproduction. According to the liberal view of human value, a behavior is not characterized as inhuman and degrading, nor immoral, in case it is not perceived as such by the subject who participates in it or accepts it. Otherwise, an objective approach to this principle would be in case that a behavior is considered to be inhuman by social criteria and regardless of the expression of the individual’s free consent and her possible desire to continue in activities offensive to the individual.